Can urban trees reduce the impact of climate change on storm runoff? - Zabret, Katarina (Urbani izziv, 2015)
The process of urbanisation leads to significant changes in surface cover, which influence the hydrological properties of an area. The infiltration of precipitation into the soil is reduced, so that both surface water runoff and the velocity at which water travels have increased drastically. In recent decades climate change has also been observed to affect precipitation trends. Many studies have shown that the amount of rainfall is increasing and that heavy rainfall events are becoming more frequent. These changes are producing more runoff, which has to be drained. Urban trees can reduce the amount of precipitation reaching the ground due to rainfall interception, and are becoming increasingly recognized as an effective means for the regulation of storm water volumes and costs. The study measured rainfall interception in an urban area. It shows that Betula pendula can intercept 20.6% of annual rainfall, whereas Pinus nigra could intercept as much as 51.0% of annual rainfall. The advantage of rainfall interception was shown in the case of a parking lot where the planting of trees was able to reduce runoff by up to 17%.
Keywords: Betula pendula; climate change; green infrastructure; hidrologija; javni prostori; klimatske spremembe; Pinus nigra; rainfall interception; storm water runoff